Crocin protects PC12 cells against MPP+-induced injury through inhibition of mitochondrial dysfunction and ER stress. (October 2015) - Zhang, Guo-Feng; Zhang, Yi; Zhao, Gang
Abstract: The molecular machinery that mediates neuronal injury in neurodegenerative conditions such as Parkinson's disease (PD) remains to be fully deciphered, which will hopefully provide novel therapeutic targets for these disorders. Crocin, one of the water-soluble carotenoids isolated from the Crocus sativus L (saffron) stigma, has been reported to exert therapeutic potential in many disease models. Here, we establish an in vitro PD model using 1-methyl-4-phenylpyridinium (MPP + )-injured PC12 cells to investigate the protective effects of crocin. Crocin treatment significantly attenuated MPP + -induced cell injury and apoptosis with little toxicity, and these protective effects were still observed even if crocin treatment was delayed to 6 h after injury. Crocin also inhibited MPP + -induced mitochondrial dysfunction, as evidenced by preservation of mitochondrial membrane potential (MMP) and ATP synthesis, which correlates with suppressed endoplasmic reticulum (ER) stress through inhibiting ER chaperone and ER related apoptotic factors. In addition, ER calcium release and morphological changes in ER lumen after MPP + exposure were all partially prevented by crocin. By using specific targeted small interfering RNA (siRNA) to knockdown the expression of the C/EBP homologous protein (CHOP), we found that crocin-induced protection and inhibition of ER stress was mediated by inverting MPP + -induced decrease of Wnt through the CHOP pathway. Our study demonstrates a pivotal role of ER stress in mediating PD related neuronal injury via the regulation of CHOP-Wnt pathway, and suggests the therapeutic values of crocin against ER stress-associated cytotoxicity. Highlights: Crocin attenuates MPP + -induced cytotoxicity via anti-apoptotic activity. Post-injury administration of crocin is protective in MPP + -injured PC12 cells. Crocin preserves mitochondrial function after MPP + exposure. Crocin inhibits MPP + -induced ER stress in PC12 cells. Inhibition of CHOP/Wnt pathway is involved in crocin-induced protection.